1987
DOI: 10.1017/s0950268800068011
|View full text |Cite
|
Sign up to set email alerts
|

Rift Valley fever: a sero-epidemiological survey among pregnant women in Mozambique

Abstract: SUMMARYRift Valley fever (RVF) causes abortion in sheep and cattle. However, the teratogenic and abortogenic potential of RVF in humans is not known. Sera from a total of 1163 pregnant women in Mozambique were tested for RVF virus antibodies by ELISA and 28 (2 %) were found to be positive. Mothers experiencing fetal death or miscarriage (155) had the same RVF virus antibody prevalence as those with normal deliveries. Analysis of maternity histories showed some indication of increased fetal wastage among women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 9 publications
(5 reference statements)
0
21
0
Order By: Relevance
“…Surveillance of cattle in the same province in 1996 and 2001 revealed a seroprevalence of 37% and 53%, respectively [9]. A seroprevalence of 2% (28/1163) in humans was found in a study conducted from 1981 to 1983 in 8 of the 10 provinces of Mozambique [10].…”
Section: Introductionmentioning
confidence: 99%
“…Surveillance of cattle in the same province in 1996 and 2001 revealed a seroprevalence of 37% and 53%, respectively [9]. A seroprevalence of 2% (28/1163) in humans was found in a study conducted from 1981 to 1983 in 8 of the 10 provinces of Mozambique [10].…”
Section: Introductionmentioning
confidence: 99%
“…The first evidence of RVFV in Mozambique was documented as early as the 1960s ( 1 ). Endemicity was subsequently confirmed in the 1980s by a prevalence study that identified virus-specific antibodies in 2% of pregnant women ( 2 ) and in the 1990s by serosurveillance in Zambezia Province, which showed that cattle had been infected with RVFV ( 3 ). …”
mentioning
confidence: 99%
“…35 The virus has not shown direct human-to-human transmission, and there have been only a few documented cases of vertical transmission. 3638 …”
Section: Epidemiologymentioning
confidence: 99%
“…28,66,67 Even though isolated cases of vertical transmission have been documented, 3638 there appears to be no increase in apparent miscarriage in pregnant women. There is also no documented human-to-human transmission; infection of people appears to be limited to either mosquito bites or exposure to high titer animal tissues.…”
Section: Clinical Presentationmentioning
confidence: 99%